Dynamic behaviour analysis of a three pressure level heat recovery steam generator during transient operation. (October 2015) - Benato, Alberto; Stoppato, Anna; Mirandola, Alberto
Abstract: The context of the deregulated energy market and the rapid expansion of the non-predictable energy sources, are stressing the necessity of improving the flexibility of traditional power plants. Cyclic operation guarantees high profits in the short term but causes a lifetime reduction due to thermo-mechanical fatigue, creep and corrosion. In this context, combined cycle gas turbine power plants are the most concerned in flexible operation. However, the most stressed devices are in the Heat Recovery Steam Generator. For these reasons, in the present work, a procedure able to estimate the most stressed devices lifetime reduction is proposed. The core of the procedure is the power plant dynamic model. The selected test case is a 380 MW combined cycle gas turbine power plant composed by a gas turbine and a three pressure level Heat Recovery Steam Generator with reheat. The model's peculiarity is the full implementation of the components geometry. The model is able to predict the plant steady-state, part-load and dynamic behaviour. Different transient conditions are tested and the superheater lifetime reduction computed. Results show that the procedure can be considered as valuable innovative instrument to assist power plant designers and operators in order to improve the plant's flexibility. Highlights: A procedure for the estimation of the lifetime reduction is proposed. The core of the procedure is the plant dynamic model. The dynamic model of a three pressure level combined cycle is built. Different transient conditions are analysed. The high pressure superheater lifetime reduction is computed.